Pilot trials in thrombosis: Purpose and pitfalls. Issue 3 (13th June 2018) - Ikesaka, Rick; Langlois, Nicole; Carrier, Marc; Kearon, Clive; Le Gal, Grégoire
Abstract: Randomized controlled trials provide important evidence to guide clinical practice. These full‐scale trials are expensive, time consuming and many are never successfully completed. Well conducted pilot studies help with full‐scale trial design, assessment and optimization of feasibility, and can avoid the waste of resources associated with starting a full‐scale trial that will not succeed. They also provide an opportunity for capacity growth and mentorship of new investigators. It is important to appreciate that the usual goal of a pilot trial is assessment of feasibility and refinement of trial design rather than to gain preliminary evidence of efficacy. Indeed, using event rates from a pilot trial to calculate sample sizes can be misleading in therapeutic trials. Misconceptions exist that pilot trials are just "small trials, " are easy to perform, and are not worthy of publication. While, in the past, many pilot trials were poorly conducted and not followed by a full‐scale trial, by following the recommendations in the "CONSORT 2010 statement: extension to randomized pilot and feasibility trials, " high‐quality pilot trials can be performed and reported that will greatly improve the chances of successfully completing a practice‐changing trial. We propose that pilot trials are a valuable investment and describe the TRIM‐Line pilot trial (NCT03506815), a pilot study assessing the feasibility of a randomized controlled trial investigating primary thromboprophylaxis with rivaroxaban in patients with malignancy and central venous catheters, as an illustrative example of how a pilot trial in the area of thrombosis should be designed.